x+y-Z=3

Simple and best practice solution for x+y-Z=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+y-Z=3 equation:


Simplifying
x + y + -1Z = 3

Reorder the terms:
-1Z + x + y = 3

Solving
-1Z + x + y = 3

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-1Z + x + -1x + y = 3 + -1x

Combine like terms: x + -1x = 0
-1Z + 0 + y = 3 + -1x
-1Z + y = 3 + -1x

Add '-1y' to each side of the equation.
-1Z + y + -1y = 3 + -1x + -1y

Combine like terms: y + -1y = 0
-1Z + 0 = 3 + -1x + -1y
-1Z = 3 + -1x + -1y

Divide each side by '-1'.
Z = -3 + x + y

Simplifying
Z = -3 + x + y

See similar equations:

| 12+3x=33 | | x-(x*0.075)=10000 | | 7x+5=(10x+70)+3x | | 5(x+1)-2(x+2)= | | 62-7x=20+23 | | 9-2(y+4)=-2y | | X^2+10x+25=10 | | 11-7x=43-14x | | -100-4x= | | 4x-100= | | 4x^2-12x+9=7 | | -114-7x=8x+21 | | (2x-1)(3x-2)+7(4-8x)(x+5)=0 | | -100+4x= | | 2x+14=-6-8x | | 100+4x= | | 4x-9=x+5 | | -23-2x=9-10x | | 6x+9=-81-9x | | 180=(6X+12)+(2X) | | 5(1-y)=10 | | 10p^2+5p=-3 | | 10x+36-38x-47=0 | | 4k^2+10k=8 | | 3[4-2(a-2)]=3(2-4a) | | X^4+36x^2=0 | | 6y+3y= | | 5x^2+20=0 | | w^2+9w+20=0 | | 11(x+8)=3(x+20) | | y+2x=3x+y | | 3x+22=11x-66 |

Equations solver categories